Management of Energy Exchange Process on Metro Rolling Stock with On-Board Capacitive Energy Storage - Sulym A.O.; Khozia P.O.; Fomin O.V.; Bahrov O.M. (Problems of the Regional Energetics)
The object of this paper is to develop and synthesize a system for managing energy exchange processes between the overhead line, electric drive of metro vehicles, braking resistor and ca-pacitive energy storage devices. To achieve this goal, the following tasks must be completed. The first task is to create a mathematical model and to define the requirements to control system for energy exchange processes currently being developed for metro rolling stock with capacitive energy storage devices. The second task is to develop a block diagram of a control unit for ener-gy exchange processes. The third task is to synthesize a control system for energy exchange pro-cesses on metro rolling stock with capacitive energy storage devices and an algorithm for its op-eration. The fourth task is to check the functioning of the synthesized control system and its op-erating algorithm. The most significant result of the work is the improvement of the technical characteristics of the rolling stock, higher passenger safety on metro transit, minimization of electricity consumption from the overhead line by increasing the use of regenerative braking en-ergy generated by the electric drive of the train, voltage compensation in the overhead line, train operation capability in emergencies due to the implementation of the developed control system. The significance of the results obtained is a synthesis of an adaptive control system that makes it possible to monitor and manage the energy exchange processes on metro rolling stock with ca-pacitive energy storage devices, considering storage devices charging rate, the train-driving mode and the nature of the energy processes.